Research Thesis for Undergraduate Engineering Programs in the Digitalization Era: Learning Strategies and Responsible Research Conduct Road to a University Education 4.0 Paradigm - Cacciuttolo, Carlos (2023)
Many university students have doubts about how or where to start writing their undergraduate thesis work; it is common not to be clear how to identify a research problem or even towards which topic their research is oriented, and there are doubts about how to process and systematize so much information available in the era of digitalization. This article presents learning strategies to formulate a research thesis for engineering undergraduate programs, with an emphasis on the use of information and communication technologies (ICTs) toward a University Education 4.0 paradigm. The main themes and issues discussed in this article, carried out through learning strategies for students based on the scientific method, are the following: (i) Recommendations for choosing a research topic, (ii) Guidelines for problem identification and question research, (iii) Suggestions for choosing a thesis advisor, (iv) Instructions for finding suitable sources of information, (v) Structure of the table of contents for writing the thesis manuscript, and (vi) Indications for preparing an oral defense of thesis research. This article highlights recommendations and precautions directed towards professors and students with the use of the chatbot-type artificial intelligence (AI) tool called ChatGPT for the formulation of the thesis under a responsible conduct approach in research. This article concludes that the application of tutoring/guidance strategies between professors and students requires an adequate ethical use of information and communication technologies (ICTs) during the development of a research thesis to generate a comprehensive educational environment that encourages research and develops a sustainable learning process in the context of the University Education 4.0 paradigm.